Prenatal caffeine exposure induces liver developmental dysfunction in offspring rats. Issue 3 (September 2019) - He, Bo; Wen, Yinxian; Hu, Shuwei; Wang, Guihua; Hu, Wen; Magdalou, Jacques; Chen, Liaobin; Wang, Hui
Abstract : We previously showed that prenatal caffeine exposure (PCE) induces intrauterine growth retardation (IUGR) and high susceptibility to nonalcoholic fatty liver disease in offspring rats, and the underlying mechanisms are associated with fetal overexposure to maternal glucocorticoids. Herein, we aimed to verify whether PCE disrupts liver development before and after birth and explore its possible programming mechanism. In vivo, reduced fetal weights and increased IUGR rates were accompanied by fetal liver developmental dysfunction in PCE rats. Increased fetal serum corticosterone and decreased insulin-like growth factor 1 (IGF1) levels were observed. Both male and female fetal livers exhibited increased glucocorticoid function-related gene ( Gr / C / ebpα ) expression and inhibited IGF1 signaling pathway ( Igf1 / Igf1r / Akt2 ) expression. At PW6, the levels of serum corticosterone and glucocorticoid function-related genes in PCE offspring livers were decreased, while serum IGF1 and liver IGF1 signaling pathway expression were increased, accompanied by obvious catch-up growth and enhanced liver function. Furthermore, in PCE adult offspring under chronic stress, serum corticosterone and liver Gr / C / ebpα expression levels were elevated, while the serum IGF1 and liver IGF1 signaling pathway levels were decreased. In vitro, cortisol (not caffeine) upregulated GR and C/EBPα expression and downregulated IGF1R expression. The IGF1R expression downregulated by cortisol was partially reversed by GR or C/EBPα knockdown. In conclusion, PCE-induced liver developmental dysfunction in fetal rats and catch-up growth in IUGR offspring. The mechanisms may be closely associated with GR/C/EBPα upregulation and IGF1/IGF1R signaling pathway downregulation in the fetal liver, caused by intrauterine programming of the liver glucocorticoid–IGF1 axis induced by glucocorticoid overexposure.